Test sample of ceramic material micro-nano component and preparation method of test sample
By combining femtosecond laser and focused ion beam technology, the problem of low processing efficiency of ceramic micro-nano devices is solved, and efficient and accurate preparation of ceramic micro-nano devices is achieved, especially suitable for single and polycrystalline micro-corrosives of hard ceramic materials The processing of silicon devices has significantly improved the processing speed and accuracy.
Patent Information
- Application Number
- CN202411256221.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-02-07
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-27
AI Technical Summary
The processing efficiency of ceramic material micro-nano devices is low, and the existing focusing ion beam technology is difficult to meet the needs of efficient preparation of ceramic micro-nano components, especially in ceramic materials with high hardness, which has extremely low processing efficiency.
By combining femtosecond laser and focused ion beam, the Pt protective layer is deposited on the ceramic material sample, the protrusion is formed by laser cutting, and fine processing is carried out through Ga+ ion beam to form test beams and bases, improving processing efficiency and accuracy .
The processing efficiency of ceramic micro-nano devices is significantly improved, with fast processing speed and high accuracy. The size deviation of the prepared devices is no more than 7%, and a complete single crystal sample is achieved from polycrystalline samples.
Smart Images

Figure CN119198235A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of inorganic materials, specifically including hard ceramic materials and a method for processing ceramic micro-nano components, and is suitable for the fine preparation, processing, development and application of ceramic micro-nano devices in the semiconductor field. Background Art
[0002] AlON ceramic materials have become new candidate materials in the field of plasma etching due to their excellent mechanical strength, oxidation resistance, and thermal shock resistance. At the same time, they have excellent mechanical properties and optical transparency, and have broad application prospects in micro / nano-electromechanical systems. However, due to the brittleness of ceramic materials, their service reliability is low. Therefore, the study of the micro-nano properties of ceramic materials and their service characteristics under various external force conditions has always been a hot topic in ceramic material research, and it is also one of the most difficult and challenging topics.
[0003] At present, the main method for preparing ceramic micro-nano devices is focused ion beam processing. Focused ion beam is a process that uses Ga with a certain energy to + The method of processing samples with ion beams, focusing the ion beam with an electromagnetic lens to determine the processing accuracy, and processing a variety of patterns with a deflection coil, has extremely high processing accuracy and flexibility. However, for ceramic materials, the hardness is relatively high, so relying on Ga + The processing efficiency of ion beam cutting to complete ceramic micro-nano components is extremely low. Therefore, in order to accurately and efficiently prepare ceramic material micro-nano devices, it is urgent to find a new and efficient preparation method to achieve the task of efficiently completing the processing of ceramic material micro-nano devices while meeting the processing accuracy. Summary of the invention
[0004] In view of the shortcomings of the existing ion beam technology, the purpose of the present invention is to provide a new preparation method for efficiently processing ceramic micro-nano components, which has the characteristics of high efficiency, short time consumption, high precision, and customized sample morphology, and can be used in the semiconductor field. It is particularly suitable for the preparation of in-situ nanomechanical test samples of ceramic materials.
[0005] This application adopts the following technical methods:
[0006] A method for efficiently processing micro-nano components of ceramic materials comprises the following steps:
[0007] (1) Select a ceramic material sample;
[0008] (2) selecting a target area on the ceramic material sample and depositing Pt on the target area;
[0009] (3) removing ceramic materials on both sides of the target area in the length direction to form a protrusion;
[0010] (4) The bottom of the protrusion is removed to make the protrusion suspended in the air to form a test beam, and the remaining part of the ceramic material sample forms a base. Both sides of the test beam in the length direction form connecting parts, and the test beam is connected to the base through the connecting parts.
[0011] Optionally, the method further includes the following steps:
[0012] The connection portion on one side connected to the test beam is removed, so that one side of the test beam is suspended in the air.
[0013] Optionally, the method further comprises the following steps: after the step of forming the protrusion, the method further comprises:
[0014] The surrounding area of the obtained raised portion is cleaned to be flat.
[0015] Optionally, in each step of removing the ceramic material, a desired sample orientation is obtained by rotating the sample stage.
[0016] Optionally, in the step of removing the ceramic material on both sides of the target area in the length direction to form the protrusion, a laser with a power of 2-5 W is used to bombard the ceramic material on both sides of the target area in the length direction:
[0017] In the step of cleaning the surrounding area of the obtained protrusion to be flat, and in the step of removing the bottom of the protrusion to make the protrusion suspended to form a test beam, an ion beam is used to remove material.
[0018] Optionally, the ion beam is Ga + Ion beam;
[0019] In the step of forming the test beam, the outer surface material of the test beam is repeatedly removed to make the test beam close to a desired size.
[0020] Optionally, in the step of removing material by ion beam,
[0021] The voltage of the ion beam is 30 kV, and the current of the ion beam is between 1.5 nA and 100 nA.
[0022] Another aspect of the present application also discloses a test sample of a micro-nano component of a ceramic material, which can be realized by the above method, and comprises: a test beam, a base and a connecting portion formed on the same ceramic material;
[0023] The test beam is supported on the base through the connecting portion, and the connecting portion is connected to at least one end of the test beam.
[0024] Optionally, the test beam is in the shape of an elongated strip, the length of the test beam is in the range of 12 to 35 μm, the width of the test beam is in the range of 0.5 to 1.5 μm, and the distance from the base is in the range of 0.5 to 1.5 μm.
[0025] The advantages and beneficial effects of the present invention are as follows:
[0026] With the help of EBSD orientation of hard ceramics with large grain size in step (2), it is possible to prepare complete single crystal samples from polycrystalline samples.
[0027] With the femtosecond laser system in step (4), by selecting the processing parameters appropriately, it is possible to achieve a higher yield than using only Ga + The processing efficiency is increased by nearly 5 times, and the device preparation with high processing speed and high precision is realized. The method of the present invention is suitable for the processing of single crystal and polycrystalline micro-nano devices of hard ceramic samples. With the laser-focused ion beam system, the size deviation of the prepared device is no more than 7%, and the speed is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The Pt deposition in a specific area of the sample
[0029] Figure 2 It uses laser cutting on both sides of the length direction
[0030] Figure 3 This is the morphology after laser cutting along the length direction
[0031] Figure 4 It's Ga + Cut along the length direction to smooth the topography on both sides of the length direction
[0032] Figure 5 This is the sample morphology after removing the bottom of the raised part and finishing.
[0033] Figure 6 This is a side view of the test cantilever beam.
[0034] Figure 7 This is the front view of the cantilever beam without laser processing.
[0035] Figure 8 This is the main view of a small cantilever beam.
[0036] Fig. 9 This is the complete morphology of the cantilever beam with one side open after the bottom of the sample is slotted
[0037] Fig.10 This is the in-situ bending test diagram of AlON transparent ceramic single crystal cantilever beam
[0038] Fig.11 These are the images of the AlON single-edge notched beam before and after in-situ testing. DETAILED DESCRIPTION
[0039] In order to more clearly illustrate the objectives, schemes and advantages of the embodiments of the present invention, the technical scheme of the AlON transparent ceramic embodiment will be described in detail and clearly in conjunction with the accompanying drawings. Obviously, the embodiments only represent a part of the present invention, not all of it. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without performing creative work are protected by the present invention.
[0040] Example 1
[0041] In this example, AlON transparent ceramic is used as the starting material to prepare a 35×1.5×1.5 μm long×width×height 3 The single crystal cantilever beam on the left and right. This embodiment uses the Carl Zeiss laser-focused ion beam system, which is based on the traditional focused ion beam and is equipped with a femtosecond laser. The femtosecond laser can eliminate thermal damage (heat-affected zone) on the sample surface and effectively improve the processing rate.
[0042] Specific steps are as follows Figure 1 As shown:
[0043] 1. Use diamond polishing materials with particle sizes of 15, 9, 3, and 1 to grind and polish AlON transparent ceramics. After polishing, place the sample in an ion polisher and polish until the confidence index of the Kikuchi pattern under the EBSD probe is greater than 0.5.
[0044] 2. Place the sample in a scanning electron microscope equipped with an EBSD probe and select a characteristic area for EBSD signal acquisition. After the signal acquisition is completed, the data is processed and analyzed to obtain the three low-index crystallographic orientations in the polycrystalline area, which are:
[0045] <001> , <110> , <111> .
[0046] 3. Fix the sample on the horizontal sample stage with conductive glue and place it in the Zeiss laser-focused ion beam electron microscope system. Determine the low index area marked in step 2 under the electron beam, and deposit a Pt protective layer with a thickness of about 100nm on the low index area at a processing voltage of 30kV to prevent the sample from being damaged by the ion beam. Figure 1 The size of the protective layer is 45×7.5μm in length×width. 2 .
[0047] 4. Because AlON transparent ceramics have a high hardness, femtosecond laser is first used to remove the material on both sides of the length direction of the Pt deposition area to form a convex part. The material removal on both sides of the length direction is divided into three steps. (1) Laser rough processing:
[0048] The energy is 4W, the speed is 30mm / s, the frequency is 20KHz, and the removal dimensions in the length direction of both sides are 150×100×100μm in length×width×height. 3 , the sample thickness in the middle is 25μm. (2) Laser rough machining: energy is 3W, speed is 10mm / s, frequency is 5KHz, and the length direction of both sides is removed with a size of 150×100×100μm. 3 , the sample thickness in the middle is 20μm. (3) Laser front and back fine processing: energy is 2W, speed is 5mm / s, frequency is 2KHz, and the length direction of both sides is removed with a size of length × width × height of 150×100×100μm. 3 , the thickness of the sample retained in the middle is 15 μm, such as Figure 2 If Ga + This step takes 5 times longer than laser processing.
[0049] 5. Use Ga on both sides of the length direction of the raised part of the sample + The ion beam performs rough machining and finishing to make both sides smooth, such as Figure 3-4 shown. Ga + Processing parameters are: voltage 30kV, rough machining current 50nA ~ 100nA, fine machining current 3nA ~ 10nA. The middle size length × width is 70 × 7μm 2 .
[0050] 6. Utilize Ga + The ion beam cuts the bottom of the raised portion, interrupting the bottom and one side of the raised portion, with the interrupted portion being 35 μm away from the connection on the other side.
[0051] 7. After breaking, use Ga to fix the bottom and top of the suspended protrusion. + Ion beam roughing and finishing are repeated to cut to the target height. + Processing parameters: voltage is 30kV, rough machining current is 15nA~60nA, and fine machining current is 1.5nA~3nA. Dimensions are length×width×height 35×2×1.5μm 3 .
[0052] 8. Rotate the sample stage to the starting position and cut the sample to the target width. The result is as follows: Figure 6 As shown. Finishing ions
[0053] The beam voltage is 30 kV, and the processing current is 100 pA to 700 pA. The dimensions are 35 × 1.5 × 1.5 μm in length × width × height. 3 .
[0054] 9. Figure 7This is a cantilever beam that was cut using only Ga+ without laser. Figure 6 There are many more amorphous materials on the surface.
[0055] 10. At the same time, we successfully prepared a 12×0.5×0.5μm long×width×height 3 Small size cantilever beams, such as Figure 8 shown.
[0056] Example 2
[0057] In this example, AlON transparent ceramic is used as the starting material to prepare a 20×0.8×2.6 μm long×width×height 3 Single crystal single-edge notched beam.
[0058] Specific steps are as follows Figure 3 As shown:
[0059] 1. Use diamond polishing materials with particle sizes of 15, 9, 3, and 1 to grind and polish AlON transparent ceramics. After polishing, place the sample in an ion polisher and polish until the confidence index of the Kikuchi pattern under the EBSD probe is greater than 0.5.
[0060] 2. Place the sample in a scanning electron microscope equipped with an EBSD probe and select a characteristic area for EBSD signal acquisition. After the signal acquisition is completed, the data is processed and analyzed to find the three low-index crystal directions in the polycrystalline area, which are: <001> ,
[0061] <110> , <111> .
[0062] 3. Fix the sample on a horizontal sample stage with conductive glue and place it in a Carl Zeiss laser-focused ion beam electron microscope system. Determine the low index area marked in step 2 under the electron beam. Deposit a Pt protective layer with a thickness of about 100nm on the low index area at a processing voltage of 30kV to prevent the sample from being damaged by the ion beam, such as Figure 1 As shown, the size of the protective layer is 45×7.5μm in length×width. 2 .
[0063] 4. Because AlON transparent ceramics have a high hardness, femtosecond laser is first used to remove the material on both sides of the length direction of the Pt deposition area to form a convex part. The length direction material removal is divided into 3 steps. Laser rough processing 1: energy is 4W, speed is 30mm / s, frequency is 20KHz, and the length direction groove size is length × width × height 150×100×100
[0064] μm 3, the width of the sample retained in the middle is 25μm. Laser rough processing 2: energy is 3W, speed is 10mm / s, frequency is 5KHz, and the length direction groove size is length × width × height 150×100×100μm 3 , the width of the sample retained in the middle is 20μm. Laser fine processing: energy is 2W, speed is 5mm / s, frequency is 2KHz, and the size of the double-sided slot is length × width × height 150×100×100μm 3 , the width of the sample retained in the middle is 15 μm, such as Figure 2 shown.
[0065] 5. Use Ga on both sides of the raised part in the length direction + The ion beam performs rough machining and finishing to make both sides smooth, such as Figure 3-4 shown. Ga + Processing parameters: voltage is 30kV, rough machining current is 50nA~100nA, and fine machining current is 3nA~10nA. The middle size is 70×7μm in length×width. 2 .
[0066] 6. Utilize Ga + The ion beam removes the bottom of the raised part and breaks the bottom of the sample. The breaking area is 5 μm from the height, and only the two sides are connected to the bulk sample. Figure 5 shown.
[0067] 7. After breaking, the bottom and top of the obtained raised structure in the height direction are measured using Ga + Ion beam roughing and finishing are repeated to cut to the target height. + Processing parameters: voltage is 30kV, rough machining current is 15nA~60nA, and fine machining current is 1.5nA~3nA. Dimensions are length×width×height 20×1.2×2.6μm 3 .
[0068] 8. Rotate the sample stage to the initial angle and cut the sample to the target width. The finishing ion beam voltage is 30kV and the processing current is 100pA to 700pA. The dimensions are 20×0.8×2.6μm in length×width×height. 3 .
[0069] 9. As Fig. 9 , use a 45° pre-tilt table and tilt the equipment to process the bottom of the sample (groove in the middle). The finished sample morphology is as follows Fig. 9 .
[0070] It can be seen from the above embodiments that the advantages and beneficial effects of the present invention are as follows:
[0071] With the help of EBSD orientation of hard ceramics with large grain size in step (2), it is possible to prepare complete single crystal samples from polycrystalline samples.
[0072] With the femtosecond laser system in step (4), by selecting the processing parameters appropriately, it is possible to achieve a higher yield than using only Ga + The processing efficiency is increased by nearly 5 times, and the device preparation with high processing speed and high precision is realized. The method of the present invention is suitable for the processing of single crystal and polycrystalline micro-nano devices of hard ceramic samples. With the laser-focused ion beam system, the size deviation of the prepared device is no more than 7%, and the speed is greatly improved.
Claims
1. A test sample of a ceramic material micro-nano component, characterized in that: include: Test beams, bases and connections formed from the same ceramic material; The test beam is supported on the base through the connecting portion, and the connecting portion is connected to at least one end of the test beam.
2. The test sample according to claim 1, characterized in that The test beam is in the shape of an elongated strip, the length of the test beam is in the range of 12 to 35 μm, the width of the test beam is in the range of 0.5 to 1.5 μm, and the distance from the base is in the range of 0.5 to 1.5 μm.
3. A method for preparing a test sample of a ceramic material micro-nano component, characterized in that: The steps include: (1) Select a ceramic material sample; (2) selecting a target area on the ceramic material sample and depositing Pt on the target area; (3) removing ceramic materials on both sides of the target area in the length direction to form a protrusion; (4) The bottom of the protrusion is removed to make the protrusion suspended in the air to form a test beam, and the remaining part of the ceramic material sample forms a base. Both sides of the test beam in the length direction form connecting parts, and the test beam is connected to the base through the connecting parts.
4. The preparation method according to claim 3, characterized in that: The following steps are also included: The connection portion on one side connected to the test beam is removed, so that one side of the test beam is suspended in the air.
5. The preparation method according to claim 3, characterized in that: The method further comprises the following steps: after the step of forming the protrusion, the method further comprises: The surrounding area of the obtained raised portion is cleaned to be flat.
6. The preparation method according to claim 3, characterized in that: During each step of removing the ceramic material, the sample stage is rotated to obtain the desired sample orientation.
7. The preparation method according to claim 5, characterized in that: In the step of removing the ceramic material on both sides of the target area in the length direction to form the protrusion, a laser with a power of 2-5W is used to bombard the ceramic material on both sides of the target area in the length direction: In the step of cleaning the surrounding area of the obtained protrusion to be flat, and in the step of removing the bottom of the protrusion to make the protrusion suspended to form a test beam, an ion beam is used to remove material.
8. The preparation method according to claim 7, characterized in that: The ion beam is Ga + Ion beam; In the step of forming the test beam, the outer surface material of the test beam is repeatedly removed to make the test beam close to a desired size.
9. The preparation method according to claim 8, characterized in that: In the step of removing material with an ion beam, The voltage of the ion beam is 30 kV, and the current of the ion beam is between 1.5 nA and 100 nA.
10. The preparation method according to any one of claims 3 to 9, characterized in that: In the step of selecting a ceramic material sample, a ceramic sample with a grain size greater than 50 μm is selected; The selected ceramic samples are AlON ceramic samples; Before the step of depositing Pt in the target area, the following steps are also included: Performing ion polishing on the surface of the ceramic material sample; The crystallographic orientation of the target area was determined using the EBSD testing method.
